Students’ Perceptions on The Use of Songs in Spotify Application toward Their Idiomatic Expressions - Divanauli, Diannisa; Supriusman, Supriusman; Dahnilsyah, Dahnilsyah (Journal of Educational Sciences, 2025)
The using of slangs or any other idiomatic expressions like phrasal verb is usually found in students’ communications nowadays. Song is one of media that influenced the using of slangs or any other idiomatic expressions. The participants of this study were the third semester students of Universitas Riau batch 2023. This study aims to find out students’ perceptions on the use of songs in Spotify Application on their idiomatic expression. This study used quantitative descriptive research design. Additionally, the data were collected through questionnaire with validity and reliability tested. The aspects of the questionnaire looking for students’ perceptions in three aspects; idiomatic expressions, English songs belief and Spotify application using. The results of this study revealed that third-semester students of Universitas Riau have positive perceptions based on mean calculation. Recommendations for students, educators and future researchers were included to supply the use of technology in language learning especially Spotify application.